The internet of things software architectural solutions - Khalefa, Mustafa S.; A. Jabar, Marzanah; Hussein, Waleed Noori; Alasad, Hamid Ali Abed; Zmezm, Hamzah F. (American-Eurasian Network for Scientific Information, 2015)
The Internet of Things (IoT) is an ambiguous term. There are different definitions for this term, ranging from any system that has sensors and actuators to a solitary interconnected network of physical items. This Paper shows that this term does not give enough information to construct a software architecture on. This is accomplished by taking an inside look at the IoT described in literature as well as the types of applications that exist on the market today and using the concept of software architectural styles to show how different areas in the IoT will need varying styles. This paper continued to classify solutions in the Internet of Things into different classes. The outcomes are that for a subset of the classes there is a reasonable style, however for remaining classes there are still different decisions where more context information is needed.